TheRole of libraries in enhancing research visibility of academics - Dang, Tihyaunin (Beau Bassin, Mauritius : LAMBERT Academic Publishing, 2017)
Despite so many researches stemming from most African Higher Educational institutions, not many are visible. This may be attributed to low quality of research works and lack of subscription fees to journals and other publishing bodies. This short practical book discusses libraries$1 (Brole in promoting the quality of research. Also, several tasks were discussed which may lead to increasing visibility of research output. The book also offers a brief on the importance of open access and how the results, impact and progress of research is accelerated through open access. Taking advantage of technology towards adding value of the works librarians are already committed to is a fact that must be realized. Knowledge enclosed here will be very useful to practicing Librarians, Information Professionals, Libraries, Higher Institutions, upcoming Professionals in the field of Librarianship and consequently, the Academics.s
Includes bibliographical references.
oif 21/01/2020
Loans
Keywords: Academic Libraries; Institutional repositories; Open access; Research; Researchers; Visibility; Higher Institutions; Librarian; Libraries